2020
DOI: 10.2106/jbjs.19.00930
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends in Orthopaedic Surgery Residency Applications and Match Rates

Abstract: Background:The current U.S. orthopaedic residency application process is becoming increasingly impersonal in the wake of an increasing number of applications. Through an analysis of orthopaedic surgery residency application statistics, we have highlighted the effect that the number of orthopaedic applications has on match rate, and we have suggested methods for a more personalized application process.Methods: Data from the Association of American Medical Colleges (AAMC) and the National Resident Matching Progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(122 citation statements)
references
References 15 publications
3
119
0
Order By: Relevance
“…However, matching into orthopedic surgery has become increasingly more competitive each year, which has led some medicals students to commit to orthopedic surgery from the onset of their medical school experiences, in order to position themselves as a more competitive applicant. 4 , 18 , 19 A previous study reported that 51% of fourth year medical students and interns who selected orthopedics, had already decided to pursue this field prior to their third-year rotation. 20 , 21 In a published commentary of the orthopedic residency applications “arms race,” Dr. Joseph Zuckerman notes, “students already are specializing too early.” Instead of going to medical school to become a physician first and an orthopedic surgeon second, many seem to bypass the physician part.…”
Section: Disruptions Of Medical Clerkshipsmentioning
confidence: 99%
“…However, matching into orthopedic surgery has become increasingly more competitive each year, which has led some medicals students to commit to orthopedic surgery from the onset of their medical school experiences, in order to position themselves as a more competitive applicant. 4 , 18 , 19 A previous study reported that 51% of fourth year medical students and interns who selected orthopedics, had already decided to pursue this field prior to their third-year rotation. 20 , 21 In a published commentary of the orthopedic residency applications “arms race,” Dr. Joseph Zuckerman notes, “students already are specializing too early.” Instead of going to medical school to become a physician first and an orthopedic surgeon second, many seem to bypass the physician part.…”
Section: Disruptions Of Medical Clerkshipsmentioning
confidence: 99%
“…5 This problem is not unique to obstetrics and gynecology; other specialties seek to discourage overapplication to allow for a more in-depth review of applications. 3,7 The AAMC publishes the number of programs needed to apply to successfully match. 8 The ''point of diminishing returns'' (PDR) varies by specialty, type of medical school, and Step 1 score.…”
Section: Discussionmentioning
confidence: 99%
“…41,44,45 The cited advantages of application caps include cost-savings to applicants and decreased application volume for programs, presumably facilitating holistic review. 5,24,[26][27][28]39 Challenges include determining the optimal cap and limited program data currently available to inform applicant decisions. 40 Signaling Program Preference: Eleven articles promoted supplemental applications to express program preference, including a program-specific paragraph in the personal statement, written or video statements of interest, or secondary applications.…”
Section: Reforms To the Application Submission Processmentioning
confidence: 99%
“…40 Signaling Program Preference: Eleven articles promoted supplemental applications to express program preference, including a program-specific paragraph in the personal statement, written or video statements of interest, or secondary applications. 4,18,[26][27][28]40,41,[46][47][48][49] This proposal frequently co-occurred with application caps (n ¼ 7) as a mechanism for reducing application volume through their time-intensive nature. 24,50,51 However, requiring applicants to submit these materials results in an increase in resources needed for application review.…”
Section: Reforms To the Application Submission Processmentioning
confidence: 99%